Exegetical exploration of 1 John 4:7–21 in the context of the Nigerian church - Ngele, Omaka K.; Unachukwu, Daniel C. (Neotestamentica, 2020)
This article examines 1 John 4:7-21 in the context of the Nigerian church. The pericope presents the elaborate nature and essence of divine love among Christians. This model of love is based on self-sacrifice, motivated by positive will and implemented by daily practice. Adopting a historical-critical method of exegesis, the article argues that a thorough understanding of this model of love in its reading of the pericope is achieved within the framework of an internal problem the Johannine community faced. This problem was rooted in the activities of heretical teachers who brought about a spiritual aristocracy and schism in the community. In this study, it is contended that 1 John 4:7-21 deals with this problem and that its teachings centre on God's love as the function of love within the Christian brotherhood. The hermeneutics of the study shows that there is a paradigm shift with regard to the conception and application of love in the Nigerian church today. It also demonstrates that most Christians in the Nigerian church consider some limitations and initiate some reservations in the practice of love to their fellow Christians. All these are against the teachings of this Johannine pericope as interpreted in this article. First John 4:7-21 teaches Christians to love one another unconditionally as the evidence of their love for God.
free
Keywords: 1 John 4; 7-21; Brotherhood; Christians in Nigeria; Church schism; God is love; Nigerian church; love one another